PENDETEKSI SERANGAN DDoS (DISTRIBUTED DENIAL OF SERVICE) MENGGUNAKAN HONEYPOT DI PT. TORINI JAYA ABADI - Saleh Dwiyatno; Ayu Purnama Sari; Agus Irawan; Safig Safig (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
Information security is very important in today's technology. Information storage and crossing is currently no longer using paper media, but has used a lot of computer and internet media. PT. Torini Jaya Abadi is one that uses computer and internet media for information storage and crossing. However, there are disturbances such as heavy server access, which cannot be accessed and sometimes it cannot enter into the database server from the indication that the server might be exposed to a virus or DDoS (Distributed Danial of Service) type attacks occur on the server. Based on these problems, the author uses a honeypot to detect an attack based on alerts that have been accommodated in the log and can also provide information about the attacks that occur, from the results obtained honeyd is able to resemble an original system that pretends to have services that are not real , also able to detect attacks in real time and provide information from attackker, honeyd can emulate virtual hosts that are similar to the original computer, by obtaining logs from the honeyd admin system to find out information that occurs on the server, with honeyd network systems can help detect attacks in real time.